Implementasi Pembelajaran Berbasis Inkuiri pada Mata Pelajaran IPS dan Pengaruhnya terhadap Hasil Capaian Pembelajaran Siswa - Safitri, Muthia Dewi; Ningsih, Tutuk (ARZUSIN, 2025)
Education has an important role in forming a generation that has the ability to think critically, analytically, and solve problems. However, in social studies learning in schools, there are still many teachers who use conventional learning, so that learning is less effective. The purpose of this study is to describe the implementation of inquiry-based learning in social studies subjects and describe its influence on student learning outcomes. This research was conducted at MI Ma'arif NU 1 Pancasan, Ajibarang District, Banyumas Regency, the subjects in this study were grade IV students totaling 27 students. This study uses descriptive qualitative research, with the type of field research. The research data was obtained through interviews and observations, then the analysis techniques included the stages of reduction, data presentation and conclusion. The results of the research obtained by the researcher related to the implementation of inquiry learning carried out by teachers are carried out through 5 stages: 1) Student orientation to problems, 2) Managing the learning process, 3) Providing investigation guidance, 4) Presenting learning results, 5) Evaluation and reflection of activities. Inquiry learning has a positive effect on student learning outcomes, including encouraging students' enthusiasm and curiosity so that they are actively involved during the teaching and learning process, fostering an independent, creative attitude, and being able to develop students' ability to think critically.